Estimating the effect of a retraining program on the re-employment rate of displaced workers - Sandra Cavaco; Denis Fougère; Julien Pouget (Institute for the Study of Labor (IZA), 2009)
In this paper we estimate by matching techniques the effects of a French retraining program on the reemployment rate of displaced workers. This program, called Conventions de conversion, was intended to improve reemployment prospects of displaced workers by proposing them retraining and job seeking assistance for a period of six months beginning just after the dismissal. Our empirical analysis is based upon non-experimental data collected by the French Ministry of Labour. Matching estimates show that this program succeeded in increasing the employment rate of trainees by approximately 6 points of percentage in the medium-term, namely in the second and third years after the date of entry into the program. This improvement is essentially due to an increase of their reemployment rate in regular jobs, namely jobs under long-term labour contracts.
urn:nbn:de:101:1-2009062287
Keywords: C41; J24; J64; J68; 330; Evaluation; retraining program; displaced workers; matching estimates; Arbeitslosigkeit; Arbeitsmarktpolitik; Umschulung; Wirkungsanalyse; Berufliche Integration; Schätzung; Frankreich